Unusual thermoelectric behavior indicating a hopping to bandlike transport transition in pentacene - Germs, Wijnand Chr.; Guo, K.; Janssen, René A. J.; Kemerink, Martijn (Physical review letters, 2012)
An unusual increase in the Seebeck coefficient with increasing charge carrier density is observed in pentacene thin film transistors. This behavior is interpreted as being due to a transition from hopping transport in static localized states to bandlike transport, occurring at temperatures below ∼250 K. Such a transition can be expected for organic materials in which both static energetic disorder and dynamic positional disorder are important. While clearly visible in the temperature and density dependent Seebeck coefficient, the transition hardly shows up in the charge carrier mobility.